Exploring the Potential Anti-diabetic Properties of Rhapis excelsa through Computational Approaches - Sagheer, Iqra; Riaz, Sania; Azhar, Mahnoor; Tariq, Mariam; Masood, Hamza; Tariq, Sharjeel (BioScientific Review, 2025)
Background. Phytotherapy has been practiced against many acute and chronic diseases by different ethnic groups around the globe. Among these medicinal plants, the species of Arecaceae family stands out due to their vast economic importance. Most of the family members contain rich phytochemicals and secondary metabolites, being part of this family, Rhapis excelsa contains flavonoids, terpenoids, tannins, and many other bioactive metabolites which are believed to contribute to its medicinal properties, potentially offering therapeutic benefits against Diabetes mellitus which is a complex metabolic disorder that has become a major global health concern. The aim was to identify and select the potential bioactive compounds from Rhapis excelsa by using computational approaches for the treatment and management of DM. Methods. C-reactive protein (CRP) was selected as the target protein. Three different ligands from Rhapis excelsa underwent both physicochemical and toxicity assessments using SwissADME and ProTox-II. Computational approaches, such as molecular docking and virtual screening were used to evaluate binding affinity. Results. The leading compound identified was apigenin which was then compared to the standard anti-diabetic drug, Glibenclamide. The results indicated that apigenin and Glibenclamide have similar functions when selected as ligands against the target protein. Literature evidence also supports the anti-diabetic effects of apigenin. Conclusion. The current study identified potential phytochemical compounds from Rhapis excelsa using computational approaches for their application in diabetes drug development. Computational analyses including molecular docking and virtual screening revealed some bioactive compounds within Rhapis excelsa.